Connectivism And Constructivism Approaches To Social Learning Theory - Muhammad Ihsan Dacholfany; Imran Latif Saifi; Sabariah Sulaiman (International Journal of Education, Vocational and Social Science, 2022)
The purpose of this paper is to discuss Social learning theory (SLT) from the aspects of connectivism and constructivism, together with its pedagogical implications. The discussion intends to provide insight into the development of teaching strategies that adapt to transformation in the way students learn, communicate, and construct new knowledge. The paper, hence, covers the brief overview of both approaches underpinning the Social Learning Theory. The writing is anticipated to be helpful for future research which empirically focus on connectivism and constructivism approaches. As efforts are made in line with the aspirations of increasing engagement, improving quality, and achieving beneficial interpersonal results, collective learning, as propagated by SLT, is believed to be superior to individualistic learning.